ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PUS (PASANGAN USIA SUBUR) DALAM PEMILIHAN ALAT KONTRASEPSI DALAM RAHIM (AKDR) DI WILAYAH KERJA PUSKESMAS KOTA BUKITTINGGI TAHUN 2023 - Fitri, Media; Andriani, Desi; Fany, Fiona (Universitas Fort De Kock, 2024)
The low use of IUDs in the Bukittinggi City Health Center Work Area was recorded as still below the target for achieving IUD family planning acceptors. The general objective of this research is to determine the analysis of factors that influence PUS (Couples of Childbearing Age) in the selection of Intrauterine Contraceptives in the Bukittinggi City Health Center Work Area in 2023. The type of research used is analytical with a Cross Sectional approach. The population in this study were couples of childbearing age in the Bukittinggi City Health Center Working Area, totaling 78 people. Accidental Sampling sampling technique. Data analysis using univariate and bivariate analysis was tested with Chi Square. The research results were obtained from 78 respondents, 54 of whom had low education, 36 people with secondary education and 48 people who received sufficient information from health workers. There is a relationship between the level of education and the level of knowledge on the use of IUD contraceptives, while information or counseling from health workers has no relationship with the use of IUDs. It is hoped that health workers, especially midwives, will improve family planning counseling which can start from antenatal care. Apart from that, health workers choose the right method in providing health education and involve husbands in choosing contraceptives. Keywords : Education, Knowledge, Information, IUD